2014
DOI: 10.3136/fstr.20.167
|View full text |Cite
|
Sign up to set email alerts
|

Free and Bound Volatile Compounds in Juice and Peel of Eureka Lemon

Abstract: Free and glycosidically bound volatile compounds in different parts of Eureka lemon were studied. Free volatile compounds were extracted by solid phase microextraction (SPME). Bound volatile compounds were isolated from juice by adsorption onto an Amberlite XAD-2 column, and then hydrolyzed by almond β-glucosidase. Both the free volatile compounds and the released aglycones were analyzed by using gas chromatography-mass spectromerty (GC-MS). Gas chromatography-olfactometry (GC-O) was also used to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…The concentration of bound volatiles in peel was higher than that in pulp except in August. Similar findings were also reported in other citrus fruits 26 and mango. 27 In total, eight bound volatiles were found in both pulp and peel of Jincheng orange, namely 2-butyl-1-octanol, benzyl alcohol, heptanoic acid, octanoic acid, benzoic acid, guaiacol, p-vinylguaiacol and vanillin.…”
Section: Bound Volatile Compounds In Pulp and Peel Of Oranges During supporting
confidence: 91%
See 1 more Smart Citation
“…The concentration of bound volatiles in peel was higher than that in pulp except in August. Similar findings were also reported in other citrus fruits 26 and mango. 27 In total, eight bound volatiles were found in both pulp and peel of Jincheng orange, namely 2-butyl-1-octanol, benzyl alcohol, heptanoic acid, octanoic acid, benzoic acid, guaiacol, p-vinylguaiacol and vanillin.…”
Section: Bound Volatile Compounds In Pulp and Peel Of Oranges During supporting
confidence: 91%
“…8‐Hydroxylinalool is generated from the hydroxylation of linalool and is a precursor of lilac aldehydes and alcohols . It was reported that benzoic acid, p ‐vinylguaiacol, 8‐hydroxylinalool, isoeugenol and vanillin were also found as bound forms in peel of citrus fruits, while large differences in the concentrations of these compounds were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐five compounds (except limonene) were identified and quantified including six aldehydes, five alcohols, one aromatic hydrocarbons, one oxide, three esters, and 19 monoterpene hydrocarbons (Table ). In a previous study, totally 34 volatile compounds were found in Eureka lemon peel (Zhong et al, ). The main compounds were limonene followed by alpha pinene, beta pinene, gamma terpinene, and myrcene.…”
Section: Resultsmentioning
confidence: 92%
“…For this, many citrus cultivars have been analyzed to identify their volatile profile [20]. Several authors have studied the volatile profile of the oil from the lemon peel [22][23][24], but information on how the rootstock influences the odorous compounds is very limited.…”
Section: Introductionmentioning
confidence: 99%